Since the coefficient of the quadratic variable is missing, I obtained it from a similar question.
The system is:
- y = (1/2)x² + 2²x - 1 and 3x - y = 1
Answer:
- The two solutions are (0, -1) and (2, 5)
Step-by-step explanation:
1. Write the system
![y=(1/2)x^2+2x-1\\ \\ 3x-y=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/92elzx1kywv4ven39t339g1kh8bct5qgng.png)
2. Clear y from the second equation to solve by substitution
![y= 3x-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g68e0c85t0cv86sjfouk6vsdryannpk2qr.png)
3. Substitute in the first equation and solve for x
![3x-1=(1/2)x^2+2x-1\\ \\ (1/2)x^2+2x-3x=0\\ \\ (1/2)x^2-x=0\\ \\ x(x/2-1)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1bm2kluh4u2pfax1pgv3jbw0sdhdrt1745.png)
![x=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/7hekn15849nfrz752rdve3zqw7fwnla263.png)
![x/2-1=0\\ \\ x/2=1\\ \\ x=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bp465pd5w0nfyy2f9yatbkg7di4xmd2ahz.png)
4. Subsitute both values into the equation y= 3x - 1
- y = 3(0) - 1 = - 1 ⇒ solution (0, -1)
- y = 3(2) - 1 = 5 ⇒ solution (2, 5)